Analisis Pengelolaan Sumber Daya Manusia pada Sub Bagian Rumah Tangga terhadap Peningkatan Kinerja Pegawai di Sekretariat Daerah Toraja Utara - Alfrida Duma; Yoel Pasae; Sita Yubelina Sabandar (Lembaga Yasin AlSys, 2025)
Human Resource Management (HRM) is a strategic factor in supporting the performance of government organizations; however, practices within local bureaucracies often remain administrative and suboptimal. This study aims to examine HRM practices and their impact on employee performance in the Household Subdivision of the Regional Secretariat of North Toraja Regency. A descriptive qualitative approach was employed using purposive sampling, involving five informants comprising structural officials and staff employees. Data were collected through semi-structured interviews, non-participatory observation, and documentation, and analyzed thematically through transcription, coding, categorization, and interpretation. The findings reveal that HRM practices are still administrative in nature: workforce planning is reactive, contract staff recruitment is based on internal recommendations, training is rarely conducted, performance appraisal lacks measurable indicators, and incentives are limited. These conditions result in low achievement motivation, although supported by harmonious working relationships, adequate facilities, and a strong familial culture. Supporting factors include team cohesion and a leadership style that provides flexibility, while key challenges lie in the lack of training, non-merit-based recruitment, weak performance appraisal systems, and limited incentive budgets. The study concludes that transforming HRM toward a strategic approach is crucial through needs- and competency-based planning, merit-based open recruitment, continuous training, objective evaluation, and performance-based incentives.